Systemic food embolism in a case of atrio-esophageal fistula after alcohol ablation of the Marshall vein: A case report: Sistemska embolija s hrano zaradi atrio-ezofagealne fistule po alkoholni ablaciji Marshalove vene: prikaz primera - Ledinek, Živa; Hojnik , Marko (Acta Medico-Biotechnica, 2024)
Purpose: Ablation procedures are common and standard therapeutic interventions for symptomatic patients with persistent atrial fibrillation (AF). Various complications have been observed after the procedure, with one of the most fatal being atrio-esophageal fistula (AEF). Although rare, AEF has very high morality. Diagnosis of AEF is challenging, especially in emergency settings, because of its unspecific clinical signs, such as atypical neurological signs after food or air embolism.Case Presentation: A 46-year-old woman with a 10-year history of AF underwent ethanol infusion of the Marshall vein. Almost a month after the procedure, the patient collapsed and was brought to the emergency department with signs of right side hemiparesis. Occlusion of the left middle cerebral artery was identified with no ischemic change in brain parenchyma. During thrombectomy the patient had a sudden episode of hematemesis. After esophagogastroscopy, she was immediately transferred to the operating room for emergency surgery, but died on the operating table. Autopsy confirmed a clinical suspicion of AEF with massive gastrointestinal bleeding and systemic food embolism. We present this case to improve clinical recognition of the signs of AEF after alcohol ablation for AF. We also recommend active surveillance for patients who undergo similar procedures, including regular check-ups.